Impact of Water Source and Quality on Survival, Growth and Health of Clarias gariepinus Fingerlings Reared in Indoor Concrete Tanks - Ekaete Patrick Anwa-Udondiah; O. A. Okunade; A. S. Aboluwodi; I. O. Soboyejo; B. M. Lawal; I. A. Akintayo (Journal of Aquaculture and Fish Health, 2023)
This experiment investigated the impact of two water sources and their quality on the survival, growth and health of Clarias gariepinus fingerlings reared in indoor concrete tanks. 400 fingerlings of mean weight 15.33±3.47 g and total length 12.63±1.00 cm (mean±standard deviation) was randomly distributed into four concrete tanks of 12 m3 capacity each. Water quality was analyzed bi-weekly throughout study duration. Growth parameters such as mean weight gain (MWG), specific growth rate (SGR) and feed conversion rate (FCR) were calculated using standard procedures. At study termination, duplicate groups per treatment were assessed for survival rate and a health status check was determined by a hematological evaluation and microscopic examination of parasitic incidence. Results indicated that fish reared in water sourced from bore-hole [BH] performed comparatively significantly better in growth (p < 0.05) than fish in water from earthen pond [EP] as the MWG stood at 294.05±79.17 g for the former against 211.03±54.62 g for the latter with the survival rates for both treatments being in excess of 90%. Additionally, fish reared in EP presented with a higher infestation load of Trichodina spp., although there was no significant difference (U = 7, p > 0.05) between fish reared in EP and BH treatments with regards to their packed cell volume levels and white blood cells. The outcome of this study shed light on the impact a water source can have on the growth and health status of C. gariepinus with a recommendation of microbiological analysis of water supply from open/surface systems before usage for the African catfish aquaculture.